African Liberation and the Mythical Separation of the Political and the Economic in International Law - Shai, Pheagane Isaac (South African Yearbook of International Law, 2022)
The putative division of public international law and international economic law, as one of the fundamental causes of the unjust international legal order, has received lesser attention, while even the most devastating African-centred critiques of injustices have taken this division for granted. It is in this sense, that I would suggest that an extensive critique of the current international legal order must not skirt around the fundamental critique of the division of public international law and international economic law. However, the precondition for this line of analysis requires a prior analysis of how capitalism instantiates this division.